TRANSFORMATION OF PARENTAL AUTHORITY IN RELATIONSHIPS WITH GROWING CHILDREN: A CROSS-CULTURAL ANALYSIS - Kasimova Komila Akmalovna (JOURNAL OF NEW CENTURY INNOVATIONS, 2025)
Annotation: This article analyzes the transformation of parental authority during the process of children growing up through the lens of cross-cultural differences. It examines how cultural traditions (collectivism vs. individualism) influence the preservation of hierarchy within the family. Particular attention is paid to the dynamics of the transition from directive control to partnership and the role of globalization in changing traditional models of raising older children